Wisdom: A Cultural Demand on Older Adults in Rural and Urban Areas - Angelica García-Mendez; Samana Vergara-Lope; Roberto Lagunes-Córdoba; Sacramento Pinazo-Hernandis (Societies)
Culture encompasses, among other things, the ways of living, feeling, and thinking of a social group and is transmitted from one generation to the next. In part, this transmission is accomplished by older adults. Generative cultural demand refers to the perception that older adults have of what society and their families expect them to contribute to the benefit of younger generations and the communities in which they live. This phenomenological study explores generative cultural demand. Semi-structured interviews were conducted with 20 older adults between the ages of 61 and 89 from urban and rural areas in Mexico. The interviews were transcribed and analyzed through content analysis using the MAXQDA program. The results show that the main category of cultural demand was wisdom, conceived as the transmission of experiences, knowledge, behavior, traditions, and values, which varied by sex and by type of urban or rural area. In rural areas, women emphasized the transmission of experiences about daily life, while men focused on matters of labor; in urban areas, both men and women highlighted the transmission of personal experiences. Participants considered themselves to be appreciated, still capable of contributing to society, and as a reservoir of knowledge, traditions, values, and principles useful to future generations.